Contactless Electrical and Structural Characterization of Semiconductor Nanowires with Axially Modulated Doping Profiles. Issue 15 (18th March 2019) - Yuan, Wuhan; Tutuncuoglu, Gozde; Mohabir, Amar; Liu, Liping; Feldman, Leonard C.; Filler, Michael A.; Shan, Jerry W.
Abstract: Efficient characterization of semiconductor nanowires having complex dopant profiles or heterostructures is critical to fully understand these materials and the devices built from them. Existing electrical characterization techniques are slow and laborious, particularly for multisegment nanowires, and impede the statistical understanding of highly variable samples. Here, it is shown that electro‐orientation spectroscopy (EOS)—a high‐throughput, noncontact method for statistically characterizing the electrical properties of entire nanowire ensembles—can determine the conductivity and dimensions of two distinct segments in individual Si nanowires with axially encoded dopant profiles. This analysis combines experimental measurements and computational simulations to determine the electrical conductivity of the nominally undoped segment of two‐segment Si nanowires, as well as the ratio of the segment lengths. The efficacy of this approach is demonstrated by comparing results generated by EOS with conventional four‐point‐probe measurements. This work provides new insights into the control and variability of semiconductor nanowires for electronic applications and is a critical first step toward the high‐throughput interrogation of complete nanowire‐based devices. Abstract : A high‐throughput technique for electrical and structural characterization of individual Si nanowires (NWs) is required to achieve large‐scale applications. Electro‐orientation spectroscopy is demonstrated to fulfill this requirement by noncontact characterization of NWs with axially programmed dopant profiles. This work serves as a first step toward efficient measurement of complete nanowire device ensembles with complex dopant structures.